Mitochondrial DNA damage and vascular function in patients with diabetes mellitus and atherosclerotic cardiovascular disease. Issue 1 (December 2016) - Fetterman, Jessica; Holbrook, Monica; Westbrook, David; Brown, Jamelle; Feeley, Kyle; Bretón-Romero, Rosa; Linder, Erika; Berk, Brittany; Weisbrod, Robert; Widlansky, Michael; Gokce, Noyan; Ballinger, Scott; et al.
Abstract Objective Prior studies demonstrate mitochondrial dysfunction with increased reactive oxygen species generation in peripheral blood mononuclear cells in diabetes mellitus. Oxidative stress-mediated damage to mitochondrial DNA promotes atherosclerosis in animal models. Thus, we evaluated the relation of mitochondrial DNA damage in peripheral blood mononuclear cells s with vascular function in patients with diabetes mellitus and with atherosclerotic cardiovascular disease. Approach and results We assessed non-invasive vascular function and mitochondrial DNA damage in 275 patients (age 57 ± 9 years, 60 % women) with atherosclerotic cardiovascular disease alone (N = 55), diabetes mellitus alone (N = 74), combined atherosclerotic cardiovascular disease and diabetes mellitus (N = 48), and controls age >45 without diabetes mellitus or atherosclerotic cardiovascular disease (N = 98). Mitochondrial DNA damage measured by quantitative PCR in peripheral blood mononuclear cells was higher with clinical atherosclerosis alone (0.55 ± 0.65), diabetes mellitus alone (0.65 ± 1.0), and combined clinical atherosclerosis and diabetes mellitus (0.89 ± 1.32) as compared to control subjects (0.23 ± 0.64, P < 0.0001). In multivariable models adjusting for age, sex, and relevant cardiovascular risk factors, clinical atherosclerosis and diabetes mellitus remained associated with higher mitochondrial DNA damage levels (β = 0.14 ± 0.13, P = 0.04 and β = 0.21 ± 0.13, P = 0.002, respectively). Higher mitochondrial DNA damage was associated with higher baseline pulse amplitude, a measure of arterial pulsatility, but not with flow-mediated dilation or hyperemic response, measures of vasodilator function. Conclusions We found greater mitochondrial DNA damage in patients with diabetes mellitus and clinical atherosclerosis. The association of mitochondrial DNA damage and baseline pulse amplitude may suggest a link between mitochondrial dysfunction and excessive small artery pulsatility with potentially adverse microvascular impact.